The challenging use and interpretation of blood biomarkers of exposure related to lipophilic endocrine disrupting chemicals in environmental health studies. (1st January 2020) - Cano-Sancho, German; Marchand, Philippe; Le Bizec, Bruno; Antignac, Jean-Philippe
Abstract: The use of exposure biomarkers has been growing during the last decades, being considered the 'gold-standard' approach for individual exposure assessment to environmental chemicals. However, lipophilic endocrine disrupting chemicals (LEDC) have specific physicochemical and biological properties implying particular analytical challenges and interpretative caveats. The epidemiological literature is therefore afflicted by methodological inconsistencies and results divergences, in part due to recognised sources of exposure measurement error and misinterpretation of results. The aim of the present review is to identify external and endogenous sources of variability and uncertainty associated with the LEDC blood biomarkers in epidemiological studies. The dynamic nature of blood and an overview of the known mechanisms of transport, storage and partition of LEDCs in the organism are first described. The external sources of variability and uncertainty introduced at pre-analytical and analytical level are subsequently presented. Subsequently, we present some specific cases where the dynamics of lipids and LEDCs may be substantially modified and thus, the interpretation of biomarkers can be particularly challenging. The environmental obesogens as source of biomarkers variability is also discussed in the light of the most recent findings. Finally, different modelling approaches (statistical and pharmacokinetic models) proposed to improve the use and interpretation of biomarkers are appraised. Highlights: We discussed major sources of variability of blood biomarkers of lipophilic EDCs. The impact of metabolic disruptors on blood biomarkers is critically reviewed. Modelling approaches are appraised to support the use of blood biomarkers.